ASSESSMENT OF THE ADOPTION OF MILLET PRODUCTION TECHNOLOGIES IN YOBE STATE, NIGERIA - Idris, S. P.; Idi, S.; Bose, A. A. (Journal of Agripreneurship and Sustainable Development, 2023)
The study assessed adoption of millet production technologies in Yobe State, Nigeria. Multiple sampling techniques was used in selecting the respondents, one hundred and seventy farmers were selected. Primary data was obtained using structured questionnaires and analyzed using both descriptive and inferential statistics. The results revealed that majority of the respondents were male, married and had attended certain levels of formal education. Also, the result revealed farmers had an average age of 42.2 years. The finding further shows an average of 17.2 years of farming experience, also with an average of 9.0 persons per households. The result also shows that the respondents had different sources of income and with an average of ₦284,500.3 per annum with an average farm size of 3.1ha. The result also shows that all the respondents had adopted various forms of technologies on millet production. The result also reveals that early maturity (78.8%), fertilizer application (68.2%), planting space (65.3%) among others were the reasons for adoption of the technologies. The finding further shows that socioeconomic factors had significant influence on adoption of millet production technologies were educational level has significant coefficient and influencing adoption of millet production at P<0.05, farm size and marital status had positive coefficient and significantly influencing adoption at P<0.001 and P<0.05, respectively. High cost of inputs (74.7%), labour (72.9%) and pest/diseases (71.8%) were the major constraints faced by the farmers in millet production. The study concluded that farmers had adopted different technologies and socioeconomic factors had significant influence on adoption of technologies among the farmers. Farmers should form associations and cooperatives to pull down resources and increases their access to inputs at subsidized rates, NGOs should provide inputs at subsidized rates to farmers in the study area.